Microwave-assisted synthesis and optical property of CdMoO4 nanoparticles - Phuruangrat A. (2014)
Microwave-assisted synthesis is a novel method used to synthesize CdMoO4 nanoparticles in propylene glycol. The effects of reaction time and microwave power on phase, morphologies, and optical properties of CdMoO4 nanoparticles were studied, using X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and UVvisible spectroscopy. The present analyses proved that these crystalline powders were scheelite-type tetragonal structured CdMoO4, with the crystallite size of 1420 nm, and 4.514.73 eV band gaps, controlled by the synthetic conditions. © 2010 Elsevier Ltd All rights reserved.